عالمی امن کے قیام کے لئے اسوہ رسول صلی اللہ علیہ وسلم سے رہنمائی: Guidance from the Sirah of the Holy Prophet ﷺfor establishing global peace - Ahmad, Hafiz Javed; Saeed-Ur-Rehman, Dr. Muhammad; Mahmood, Dr. Khalid (Al-Amīr Research Journal for Islamic Studies, 2024)
The pursuit of global peace is a fundamental tenet of Islam, as exemplified through the life of the Prophet Muhammadﷺ. His teachings advocate core values such as forgiveness, love, brotherhood, unity, coexistence, and tolerance, emphasizing the importance of compassion, patience, and respect for humanity. Central to the promotion of both internal and global peace are the teachings of the Qur’an and Sunnah. The Treaty of Hudaybiyyah represents a critical juncture in early Islamic history, strategically negotiated to establish peace amid conflict, particularly when Muslims in Medina faced threats from the Quraysh of Mecca and the Jewish tribes of Khaybar. This treaty not only facilitated future interactions but also laid the groundwork for the expansion of Islam, despite its initial appearance of favoring the Quraysh. The subsequent breach of this treaty by the Quraysh culminated in the conquest of Mecca, during which the Prophet exemplified mercy by granting amnesty to the surrendering populace, thereby reinforcing the Islamic principles of forgiveness and justice. This article examines the necessity and significance of peace in light of the Qur’an and Sunnah, delves into the implications of the Treaty of Hudaybiyyah and the subsequent conquest of Mecca, and underscores the importance of upholding agreements in international relations. The life of the Prophet Muhammad ﷺ serves as a paradigm for navigating conflict and diplomacy, illustrating how compassion and justice can prevail in the quest for global peace. Keywords: Global peace; Treaty of Hudaybiyyah; Prophet Muhammad; Quraysh; Islamic history; conflict resolution; diplomacy; international relations.